Navigating a pathway of professional learning: Travelling the Hero's journey with first year pre-service teachers. (February 2023) - McKay, Loraine; Riley, Tasha; King, Jonathan; Bamford-Mareroa, Annabelle; Licence, Stacey
Abstract: Opportunities to investigate the emotionality and sensitivities of teaching are limited in initial teacher education (ITE) programs. Using the hero's journey structure, this paper reports the experiences of sixteen first-year preservice teachers (PSTs) in a 6-week pilot program. Participants volunteered at a community homework club as mentors and tutors of students who had experienced domestic violence. The PSTs' learning path was captured through a range of reflection activities undertaken before, during and after the program. Thematic analysis exposed trust and relationships as important allies on the journey, and reflective practice became an authentic tool to examine an emerging teacher identity. Highlights: Investigating the emotionality of teaching during ITE contribtes to teacher identity and self-care. Trust is a non-negotiable contextual feature of ITE to promote authentic reflection. Scaffolded work integrated learning programs help to counter the theory-practice divide within ITE. Authentic opportunities that promote creativity, reflexivity, critical thinking and self-reflection enhance teacher agency. All ITE stakeholders need to value the function of reflection in ITE beyond an assessment device.